Folk Dance Education Based on Structural Analysis in Hungary - Henrik Kovács (Muzikološki Zbornik, 2025)
The paper describes the characteristics features of a definite dance motif from Hungary, presents the framework for its re-creation used during teaching and shows the educational process. The application of the methodological principles of the education contributes to the survival of the dance, promotes the traditional improvisational re-creation of the dance that displays individuality.